Determination of the triplet state energies of a series of conjugated porphyrin oligomers. - Kuimova, M; Hoffmann, M; Winters, M; Eng, M; Balaz, M; Clark, I; Collins, H; Tavender, S; Wilson, C; Albinsson, B; Anderson, H; Parker, A; et al. (2007)
We report a systematic study of the photophysical parameters relevant to photodynamic therapy (PDT) by a new type of sensitizers, conjugated porphyrin oligomers. Due to the strong nonlinear properties of oligomers containing 2, 4 and 8 porphyrin units, these molecules are attractive candidates for PDT via multiphoton excitation. The triplet state energy levels for all molecules have been determined by the triplet quenching method, phosphorescence measurements and DFT calculations. We find that the triplet energies of all the oligomers are sufficient to generate singlet oxygen, >94 kJ mol(-1). However, low singlet oxygen quantum yields are observed for the tetramer and the octamer, as compared to the conjugated dimer and monomeric porphyrin, reflecting the decrease in triplet yield. Thus the conjugated porphyrin dimer is the most promising core structure for PDT applications via multiphoton excitation.